2017
DOI: 10.1080/2162402x.2017.1336593
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal influence of B cells and tumor macro and microenvironments in theApcMin/+model of colorectal cancer

Abstract: One of the most fascinating aspects of the immune system is its dynamism, meant as the ability to change and readapt according to the organism needs. Following an insult, we assist to the spontaneous organization of different immune cells which cooperate, locally and at distance, to build up an appropriate response. Throughout tumor progression, adaptations within the systemic tumor environment, or macroenvironment, result in the promotion of tumor growth, tumor invasion and metastasis to distal organs, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
(60 reference statements)
2
8
0
Order By: Relevance
“…This result was specific to the inflammatory condition since the simultaneous increase of activated MCs and PCs was not observed in the context of CRC. Indeed, all B cell populations considered in our analysis were less represented in the cancerous compared to the normal mucosa of CRC patients, which is in accordance with our recently published data showing the accumulation of IgA + elements in areas of low‐grade dysplasia and their extrusion from the adenoma tissue [26]. Altogether these data call for the need for a better understanding of this crosstalk that bridges the innate and adaptive immune system, with particular attention on the implications that this bidirectional interaction has on MC function.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result was specific to the inflammatory condition since the simultaneous increase of activated MCs and PCs was not observed in the context of CRC. Indeed, all B cell populations considered in our analysis were less represented in the cancerous compared to the normal mucosa of CRC patients, which is in accordance with our recently published data showing the accumulation of IgA + elements in areas of low‐grade dysplasia and their extrusion from the adenoma tissue [26]. Altogether these data call for the need for a better understanding of this crosstalk that bridges the innate and adaptive immune system, with particular attention on the implications that this bidirectional interaction has on MC function.…”
Section: Discussionsupporting
confidence: 91%
“…Single‐cell suspensions of spleens, peritoneum, and LNs were obtained as previously described [26]. Peritoneal and splenic CD19 + B cells for B/MC co‐cultures were obtained using mouse CD19 MicroBeads (Miltenyi) while the B cell isolation kit (Miltenyi) was used to isolate B lymphocytes from total RMB splenocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Since IgA-secreting cells contribute to reducing inflammatory response which is a strong risk factor for the development of gastrointestinal adenocarcinomas, it is likely that the impairment of IgA production may drive further inflammatory responses and promote tumor growth. This is consistent with prior studies that showed the influence of IgA-secreting cells and B cells to colon tumors progression [59, 60].…”
Section: Resultssupporting
confidence: 93%
“…Many of the proinflammatory cytokines are abundantly expressed in chronic inflammatory lesions and the tumor tissues, but it was reported that, unlike these proinflammatory cytokines, IL-10 is not expressed in tumor tissues ( Mumm et al, 2011 ). It is well known that IL-10 is expressed in B and T cells ( Dambuza et al, 2017 ; Mion et al, 2017 ; Yu et al, 2013 ). IL-10 is also expressed in myeloid cells such as MDSCs ( Hardbower et al, 2017 ; Shvedova et al, 2015 ) to promote tumor growth.…”
Section: Discussionmentioning
confidence: 99%